2011
DOI: 10.1177/0022034511410699
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Secretory Protein Binds Phosphatidylinositol (3,4) Bisphosphate

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…However, previous results show both bacterially expressed rat PSP and human PSP synthesized in vitro bind specifically to Phosphatidylinositol (3,4)Bisphosphate [36]. PSP bound to PI(3,4)P2 10-fold stronger than to PtdIns(3,5)P 2 or PtdIns(4)P. The ability of PSP to decorate membranes suggests additional functions and may give us more insight as to how PSP is sorted and secreted.…”
Section: Mechanism Of Parotid Gland Secretionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, previous results show both bacterially expressed rat PSP and human PSP synthesized in vitro bind specifically to Phosphatidylinositol (3,4)Bisphosphate [36]. PSP bound to PI(3,4)P2 10-fold stronger than to PtdIns(3,5)P 2 or PtdIns(4)P. The ability of PSP to decorate membranes suggests additional functions and may give us more insight as to how PSP is sorted and secreted.…”
Section: Mechanism Of Parotid Gland Secretionmentioning
confidence: 90%
“…Western blot analysis was done with independent purified samples and confirmed that PSP selectively bound to granule membranes, unlike amylase and ProlineRich Protein (PRP) [36]. When exogenous PSP was tested with digested granule membranes it still bound effectively, indicating that PSP does not require a protein receptor for binding to the membrane.…”
Section: Mechanism Of Parotid Gland Secretionmentioning
confidence: 92%
See 2 more Smart Citations
“…Cargo proteins secreted into the parotid saliva are transcribed, translated, sorted, stored, and secreted by the parotid acinar cells (Venkatesh, Goyal, Carenbauer, & Darling, 2011). These polarized cells are cone shaped and are found in clusters called acini (Baker, 2010) Figures 1A, 1B.…”
Section: Parotid Gland Acinar Cellsmentioning
confidence: 99%